Aplikasi Critical Path Method (CPM) dengan Crashing Program untuk Mengoptimalkan Waktu dan Biaya Proyek - Try Hardini Rahayu Mukti; Ika Purnamasari; Wasono Wasono (EKSPONENSIAL, 2019)
The management of small and large-scale projects requires good planning, scheduling and coordination. Critical Path Method (CPM) is one of the method that has been developed to overcome the problem of managing a project. Time and cost greatly affect the success and failure of a project. A desired project is completed within a predetermined time, it can accelerate the duration of the activity with the consequence of an increase in cost. Acceleration of project duration at the lowest possible cost is called crashing program. The purpose of this study is to determine the optimal time and cost in completing the project. The data used is the type of work and time of completion of project work and wage costs of workers wages in the project development of SMP Negeri 24 Jalan Pangeran Suryanata Samarinda. Based on the analysis using the time efficient CPM method for completion of the project is 185 days. Acceleration of project completion time by using crashing program, project can be done for 157 days with increase of worker wage equal to Rp 473,802,785.32.